The Influence of Health Promotion Media With Bimanesse Local Language on Parents and Their Families Understanding about Characteristic of Drug User - Ade Wulandari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2019)
Background: The consumption of narcotics, psychotropic and addictive substances are increased among teenagers in Bima. Efforts to prevent and suppress drug trafficking and their abuse need to be implemented continuously through the process of education and information sharing among families who has teenagers. The use of local wisdom in health promotion can be done by using media with local language. Purpose: This study aims to determine the effect of delivering information about the characteristics of drug users using the local Bima Language booklet towards family knowledge. Methods: This study was conducted by using post-test only design that use control group with 30 respondents for each group. The data was obtained by observation and interview.The data analysis used a Nonparametric Test with the Mann-Whitney test. Results: The results showed that there was no difference in understanding between respondents who read booklets in local Bima language and respondents who read booklets in Indonesian language with p = 0.058. Conclusion: The use of the Booklet in local Bima language has the same effect as the use of booklets in Indonesian language